Peningkatan Kemampuan Membaca Nyaring Kelas III Berbantuan Media Flashcard di Sekolah Dasar - ayu, gista; Fatmawati, Lia; Ermawati, Diana (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This Classroom Action Research (PTK) aims to improve the reading skills of class III students at SDN 4 Karangbener through Flash card media. The main problem faced by students is their low reading ability which is reflected in unsatisfactory reading test results and low motivation to learn to read. This research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection stages. Data collection techniques include observation sheets, interviews and test. The results of the research show that it can be seen from the results of data analysis in cycle I, as many as 8 students out of 15 total class 3 students have completed their ability to read aloud reaching 53.4% ??with an average score of 74.5. In cycle 2 the data processing results obtained increased to 13 students reaching 86.7% with an average score of 78.3. It can be concluded that there is an increase in the use of flashcard media in the ability to read aloud